Uncertainty in Detection of Volcanic Activity Using Infrasound Arrays: Examples From Mt. Etna, Italy - De Angelis, Silvio; Haney, Matthew M.; Lyons, John J.; Wech, Aaron; Fee, David; Diaz-Moreno, Alejandro; Zuccarello, Luciano (Frontiers in Earth Science, 2020)
The injection of gas and pyroclastic material from volcanic vents into the atmosphere is a prolific source of acoustic waves. Infrasound arrays offer efficient, cost-effective and near real-time solutions to track the rate and intensity of surface activity at volcanoes. Here, we present a simple framework for the analysis of acoustic array data, based on least-squares beamforming, that allows to evaluate the direction and speed of propagation of acoustic waves between source and array; we also propose a new scheme, based on error propagation theory, for the quantitative assessment of uncertainty on these measurements. We the apply the algorithms to data collected by two 6-element infrasound arrays deployed at Mt. Etna during the period July-August 2019. Our results demonstrate that the use of two infrasound arrays allowed detecting and tracking acoustic sources from multiple craters and active vents associated with degassing and ash-rich explosions, vigorous and frequent Strombolian activity, opening of new eruptive fractures and emplacement of lava flows. Finally, we discuss the potential use of metrics based on infrasound array analyses to inform eruption monitoring operations and early warning at volcanoes characterized by episodic intensification of activity.